Strain and strain rate imaging in cardiomyopathy. - Nesbitt GC; Mankad S (Echocardiography, 2009)
The most common indication for an echocardiogram is for the assessment of left ventricular (LV) function and, in the evaluation of cardiomyopathy (CM), this becomes even more important. However, conventional echocardiographic measures of ventricular function are insensitive at detecting subtle perturbations in contractility. In patients with CM, the ability to detect abnormalities early in the course of the disease to establish a diagnosis can be critical and often may influence specific treatments administered as well as establish important prognostic information. Technologic advances in echocardiographic imaging during the last decade now allow for the measurement of LV strain and strain rate (SR) imaging. Strain and SR imaging allow for a more precise characterization of the mechanics of myocardial contraction and relaxation (deformation imaging) and emerging data are establishing the use of these techniques in a variety of different cardiomyopathic conditions. After establishing a common understanding of strain imaging as well as defining the methods by which these measures can be incorporated into an echocardiographic examination, we will review the accumulating information illustrating the great promise that this imaging modality has in the care of patients with CM. This review will focus on the role of strain and SR imaging in CM.